Direct Evidence of Coal Swelling and Shrinkage with Injecting CO2 and N2 Using in-situ Synchrotron X-ray Microtomography. (November 2022) - Zhang, Guanglei; Ranjith, P.G.; Huppert, Herbert E.
Abstract: Deep coal seams are one of the world's most widespread deposits for carbon dioxide (CO2 ) disposal and are generally located near large point sources of CO2 emissions. The injection of CO2 into coal seams has great potential to sequester CO2 while simultaneously enhancing coalbed methane (CO2 -ECBM) recovery. Pilot tests of CO2 -ECBM have been conducted in coal seams worldwide with favorable early results. However, one of the main technical barriers in coal seams needs to be resolved: Injecting CO2 reduces coal permeability and well injectivity. Here, using in situ synchrotron X-ray microtomography, we provide the first observational evidence that injecting nitrogen (N2 ) can reverse much of this lost permeability by reopening fractures that have closed due to coal swelling induced by CO2 adsorption. Our findings support the notion that injecting minimally treated flue gas—a mixture of mainly N2 and CO2 —is an attractive alternative for ECBM recovery instead of pure CO2 injection in deep coal seams. Firstly, flue gas produced by power plants could be directly injected after particulate removal, thus avoiding high CO2 -separation costs. Secondly, the presence of N2 makes it possible to maintain a sufficiently high level of coal permeability. These results suggest that flue-gas ECBM for deep coal seams may provide a promising path toward net-zero emissions from coal mines.